Insulin Resistance Does Not Impair Mechanical Overload-Stimulated Glucose Uptake, but Does Alter the Metabolic Fate of Glucose in Mouse Muscle - Weyrauch, Luke A. (Int J Mol Sci, 2020)
Skeletal muscle glucose uptake and glucose metabolism are impaired in insulin resistance. Mechanical overload stimulates glucose uptake into insulin-resistant muscle; yet the mechanisms underlying this beneficial effect remain poorly understood. This study examined whether a differential partitioning of glucose metabolism is part of the mechanosensitive mechanism underlying overload-stimulated glucose uptake in insulin-resistant muscle. Mice were fed a high-fat diet to induce insulin resistance. Plantaris muscle overload was induced by unilateral synergist ablation. After 5 days, muscles were excised for the following measurements: (1) [(3)H]-2-deoxyglucose uptake; (2) glycogen; 3) [5-(3)H]-glucose flux through glycolysis; (4) lactate secretion; (5) metabolites; and (6) immunoblots. Overload increased glucose uptake ~80% in both insulin-sensitive and insulin-resistant muscles. Overload increased glycogen content ~20% and this was enhanced to ~40% in the insulin-resistant muscle. Overload did not alter glycolytic flux, but did increase muscle lactate secretion 40–50%. In both insulin-sensitive and insulin-resistant muscles, overload increased 6-phosphogluconate levels ~150% and decreased NADP:NADPH ~60%, indicating pentose phosphate pathway activation. Overload increased protein O-GlcNAcylation ~45% and this was enhanced to ~55% in the insulin-resistant muscle, indicating hexosamine pathway activation. In conclusion, insulin resistance does not impair mechanical overload-stimulated glucose uptake but does alter the metabolic fate of glucose in muscle.